Ringblitzgerät für entomologische Aufnahmen. - Adam, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The above publication deals with an electronic ring flash-light for the special purpose of insect photography based upon flash-light systems obtainable in the DDR. Constructive details for self-construction are given on the tables 8 and 9.